2022
DOI: 10.1002/advs.202105201
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxy of 2D Materials toward Single Crystals

Abstract: Two‐dimensional (2D) materials exhibit unique electronic, optical, magnetic, mechanical, and thermal properties due to their special crystal structure and thus have promising potential in many fields, such as in electronics and optoelectronics. To realize their real applications, especially in integrated devices, the growth of large‐size single crystal is a prerequisite. Up to now, the most feasible way to achieve 2D single crystal growth is the epitaxy: growth of 2D materials of one or more specific orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 180 publications
(429 reference statements)
0
31
0
Order By: Relevance
“…[13] In addition, as shown in Figure 3b, it is difficult for the defects to form at the bonding interface between fluorphlogopite and thin film in van der Waals epitaxy, which has no effect on the thin film's functionality. In Figure 3c,d, dangling bonds and vdW bonds coexist in quasi-vdW heteroepitaxy, Zhang [14] called it the quasi-vdW force, but the growth mechanism is still an interesting research avenue to be explored. As a layered material, the atoms within the layers are held together by a covalent bond, while the atoms between the layers are connected by van der Waals force.…”
Section: Mechanism Of Van Der Waals Epitaxial Growth On Fluorphlogopitementioning
confidence: 99%
“…[13] In addition, as shown in Figure 3b, it is difficult for the defects to form at the bonding interface between fluorphlogopite and thin film in van der Waals epitaxy, which has no effect on the thin film's functionality. In Figure 3c,d, dangling bonds and vdW bonds coexist in quasi-vdW heteroepitaxy, Zhang [14] called it the quasi-vdW force, but the growth mechanism is still an interesting research avenue to be explored. As a layered material, the atoms within the layers are held together by a covalent bond, while the atoms between the layers are connected by van der Waals force.…”
Section: Mechanism Of Van Der Waals Epitaxial Growth On Fluorphlogopitementioning
confidence: 99%
“…[164] It was revealed that the high stability of sapphire substrate inhibited the atomic movement of the surface sapphire resulted in a slight lattice offset of the neighboring aligned WS 2 islands. [165] Since synthesis of MCs has been focused on WS 2 , MoS 2 , MoSe 2 , and WSe 2 , the validity of the step-edge guided growth should be investigated for other MCs. The 2D islands on a liquid substrate are free to rotate, hence seamless stitches are easier than on the solid substrate.…”
Section: Multi-nucleation Approachmentioning
confidence: 99%
“…VdWe is a process in which an upper film and substrate are combined by van der Waals forces, which is different from traditional epitaxy, where interfacial chemical bonding forms between the film and substrate (20,21). However, the bond strength of van der Waals forces is normally one to two orders of magnitude lower than that of chemical bonds (22,23). Therefore, it is difficult to achieve highly oriented nucleation and growth of single-crystal III-nitride films on graphene through van der Waals forces.…”
Section: Introductionmentioning
confidence: 99%